Geometrical metrology for metal additive manufacturing. Issue 2 (2019) - Leach, R.K.; Bourell, D.; Carmignato, S.; Donmez, A.; Senin, N.; Dewulf, W.
Abstract: The needs, requirements, and on-going and future research issues in geometrical metrology for metal additive manufacturing are addressed. The infrastructure under development for specification standards in AM is presented, and the research on geometrical dimensioning and tolerancing for AM is reviewed. Post-process metrology is covered, including the measurement of surface form, texture and internal features. In-process requirements and developments in AM are discussed along with the materials metrology that is pertinent to geometrical measurement. Issues of traceability, including benchmarking artefacts, are presented. The information in the review sections is summarized in a synthesis of current requirements and future research topics.